Quantitative Assessment of Interest Rate Fluctuation Sensitivity in Nigerian Insurance Asset-Liability Management - Adewale, Taiwo Abiodun; Tinuoye, Oladipo Abiodun; Adebayo, Ajala Olusegun; Oluwaseyi, Olaiya Olumide; Olalekan, Owoade Olusegun; Damilare, Olaleye Peter (Mikailalsys Journal of Mathematics and Statistics, 2025)
This study investigates the sensitivity of insurance portfolios to interest rate fluctuations in Nigerian insurance companies, with particular focus on the implications for asset and liability valuation. The objective is to assess how interest rate variability affects the relative sensitivities of assets and liabilities, and the resulting solvency risks. A quantitative approach was adopted, using a sample of ten insurance companies selected based on asset base and data availability. Data covering a ten-year period (2013–2023) were obtained from published financial statements and Central Bank of Nigeria interest rate bulletins. Analytical techniques included stochastic simulations and regression modeling, applying the Vasicek and Heston frameworks, with visualization performed using Python 3.12.3. The results show that liabilities exhibit greater sensitivity to interest rate fluctuations than assets, with pronounced volatility under stress scenarios, thereby creating significant solvency challenges. These findings validate the importance of dynamic stochastic models in capturing the complexities of interest rate effects, as opposed to static mathematical assumptions. The study concludes that effective asset–liability management (ALM) requires robust dynamic interest rate modeling. Theoretical contributions include extending the application of stochastic differential equations to emerging market contexts, while practical recommendations urge insurance regulators and investment managers to adopt interest rate-sensitive frameworks for risk management and capital adequacy assessments. Future research is recommended on macroeconomic stress factors and stochastic volatility models tailored to African financial markets.